2020
DOI: 10.1002/pol.20190115
|View full text |Cite
|
Sign up to set email alerts
|

Controllable synthesis of silica nanoparticle size and packing efficiency onto PVP‐functionalized PMMA via a sol–gel method

Abstract: This study aimed to investigate synthesis and adsorption behavior of silica nanoparticles onto polyvinylpyrrolidone (PVP)‐functionalized poly(methyl methacrylate) under various conditions such as methanol/water ratio, ammonium hydroxide concentration, polymer contents, tetraethylorthosilicate contents, and total volume of solvent via sol–gel method. First, the copolymerization of methyl acrylate as a comonomer and 1‐dodecanethiol as a chain transfer agent increased the thermal stability of the product; however… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Therefore, the incorporation of silica nanoparticles in the CNFs makes the colloidal solution relatively more stable than CNFs alone. Previous studies have shown that silica nanoparticles are in a relatively more stable state at around −60 mV in a pH solution [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, the incorporation of silica nanoparticles in the CNFs makes the colloidal solution relatively more stable than CNFs alone. Previous studies have shown that silica nanoparticles are in a relatively more stable state at around −60 mV in a pH solution [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a previous work, it was found that increasing the water content resulted in an increase in the silica particle size and a decrease in the packing efficiency. Silica nanoparticles are generated and stabilized in an excess of an aqueous solution, which decreases their adsorption on the CNF surface [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 1 shows the SEM and TEM images of the PMMA/silica hybrid particles. PMMA particles have an average particle size and standard deviation of approximately 716 nm and 0.138, respectively [ 40 ]. PMMA/silica hybrid particles have a silica particle size and silica content of approximately 23 nm and 18 wt.%, respectively.…”
Section: Methodsmentioning
confidence: 99%